Mitigation of Coal Mining Dust Impact: A Focus on Aceh Province’s Environmental Policy - Desi Marlizar; Yunita Yunita (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to examine the strategies implemented by the Environment Agency in addressing the impacts of dust on the environment, which is prompted by the presence of coal mining companies in West Aceh, with a case study in Gampong Peunaga Cut Ujong. The method used in this research is descriptive qualitative with data collection through observation, interviews, and documentation, involving the community and relevant parties. The results of the study indicate that the strategies undertaken include environmental management, supervision of mining companies, implementation of technology, resources used by the agency, as well as SOPs and authorities that are the focus in the management and control by the Environment Agency. The strategies encompass four main aspects: organizational strategy, program strategy, resource support strategy, and institutional strategy. In the organizational strategy, the office has conducted impact identification, received public complaints, and performed periodic evaluations based on the AMDAL documents, but its implementation still requires improved consistency. Program strategies such as air quality monitoring, implementation of dust control technologies, and greening efforts are underway, but their results have not been entirely effective due to limited area coverage. Supporting strategies still face challenges related to resource limitations in manpower and technology at the regional/district level. Meanwhile, institutional strategies leverage existing regulations and SOP, but their implementation has not been fully optimized in the field.